2010
DOI: 10.1007/s00264-010-1150-1
|View full text |Cite
|
Sign up to set email alerts
|

Excellent results with cementless total hip arthroplasty and alumina-on-alumina pairing: minimum ten-year follow-up

Abstract: Ceramic-on-ceramic coupling is thought to be a durable alternative to metal- or alumina-on-polyethylene pairing. No evidence exists suggesting superior clinical and radiological results for hydroxyapatite-coated stems versus uncoated stems. The aim of this study is to report the performance of an alumina-on-alumina bearing cementless total hip arthroplasty and to compare stems with a tapered design with and without hydroxyapatite coating. We prospectively analysed the results of cementless tapered femoral stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 25 publications
7
22
0
Order By: Relevance
“…Our results are consistent with those from other studies on ceramic-on-ceramic bearing [10,11,[29][30][31][32][33][34] and ceramic-on-highly cross-linked polyethylene bearing [3][4][5]9]. The most common potential causes of thigh pain are instability of the femoral stem and a tight distal fill by a rigid femoral stem [3,4,6,34].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are consistent with those from other studies on ceramic-on-ceramic bearing [10,11,[29][30][31][32][33][34] and ceramic-on-highly cross-linked polyethylene bearing [3][4][5]9]. The most common potential causes of thigh pain are instability of the femoral stem and a tight distal fill by a rigid femoral stem [3,4,6,34].…”
Section: Discussionsupporting
confidence: 83%
“…Strategies to reduce wear have focused on improvements in the bearing surface such as ceramic-onceramic or ceramic-on-highly cross-linked polyethylene bearings. Several studies have demonstrated that contemporary ceramic-on-ceramic or ceramic-on-highly cross-linked polyethylene bearings are associated with low prevalence of osteolysis in young and active patients [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We found the survivorship of implants with alumina-onalumina bearings was 98.9% in the best-case scenario and 83.1 % in the worst-case scenario, at 10 years, which are similar to the survival rates reported for older patients [23,28,31]. Numerous reports have been published on alumina-on-alumina bearings in THAs in young patients ( Table 3).…”
Section: Discussionsupporting
confidence: 80%
“…Although the results of modern cemented or cementless total hip arthroplasty (THA) are generally good [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], thigh pain, stress shielding and periprosthetic fracture are still potential problems [2,[6][7][8][9]. In an effort to reduce the periprosthetic fracture, thigh pain, and stress shielding, an ultra-short, anatomic metaphyseal-fitting cementless femoral component was developed.…”
Section: Introductionmentioning
confidence: 99%